(untitled) (Journal of the College of Basic Education, 2025)
This study is concerned with the literary form of the poetic text and the extent to which different races overlap with it through the features and connotations that draw points in common between these races and the extent and importance of this marriage, and the aesthetic and artistic values it offers studded with creative touches that add additional beauty to it. Introduction: The creative text oscillates between the purity of gender and the intermingling of genders, and in the face of these transformations, the pendulum of the critic’s clock remains moving, questioning this phenomenon, searching for its foundations, and trying to uncover its dimensions and aesthetics. Every text that has a banner of literary creativity hanging on its walls has its own characteristics on the one hand, and other characteristics that connect it with the genres close to it, or that reside with it in the same house of the literary genre on the other hand. This movement of convergence and rapprochement continues between genres within the same literary genre or between different genres. Perhaps we come to the belief that indicates that creativity acquires the characteristic of positive interaction with the phenomenon of genre interference. The research attempts to interrogate these connotations, attempts to find these common points and the importance of intermarriage and cross-fertilization between literary genres, and what this convergence offers in terms of aesthetic and artistic values ​​that adorn the creative text with creative touches that add additional beauty to it. The focus will also be on Arabic poetry, especially ancient poetry, trying to trace the effect of cross-pollination and juxtaposition in important Arabic models that have remained fresh, tender and immortal until this date, and will continue to remain immortal. Arabic poetry possesses creative models as existing evidence. The research gives what satisfies his eagerness and waiting.